FUNCTIONAL-SEMANTIC ANALYSIS OF GARDENING TERMS IN THE UZBEK LANGUAGE - Utkirov Shoxruh Ixtiyorovich; Supervisor: Narmurodova Gulnoza (Modern American Journals, 2025)
This study examines the formation of similes and metaphors in the Uzbek language derived from lexemes associated with gardening and horticulture. It has been demonstrated that similes in Uzbek literary texts are employed extensively and convey predominantly connotative meanings. Moreover, this highlights the similarities or differences between two or more objects or concepts recognized as one of the most widely utilized logical methods for comprehending external reality.
Keywords: Gardening term, similies, metaphor, linguoculture, anthropomorphism, phytonym, figurative meaning.